(untitled) (Al-Aasar, 2025)
Early marriage remains a prevalent practice in rural Pakistan, placing young females at increased risk of psychological distress, including depression, anxiety, and stress. This study examined ethnic differences in psychological distress among married females under 18 years of age from rural Punjab and Khyber Pakhtunkhwa, including Punjabi and Pashtun participants. Using a cross-sectional correlational design, data were collected from 350 married females (aged 13–17 years) through snowball sampling, following informed consent from legal guardians. Psychological distress was assessed using the Depression, Anxiety, and Stress Scale–21 (DASS-21). Results revealed significant positive correlations among depression, anxiety, and stress. Independent-samples t-tests showed no significant differences in depression between ethnic groups; however, Pashtun females reported significantly higher levels of anxiety and stress compared to Punjabi females. The findings highlight the need for culturally sensitive mental health interventions, preventive strategies, and policies aimed at protecting the well-being and rights of young married females in rural Pakistan.